2018
DOI: 10.2485/jhtb.27.34
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyols on Phosphorus-Containing Calcium Fluoride Deposition on Hydroxyapatite Surfaces

Abstract: The present study investigated how polyols (sugar alcohols) affect the formation of calcium fluoride (CaF 2 ) in the presence of fl uoride on synthetic hydroxyapatite (HA) as a model of tooth enamel. HA plates were immersed in sugar alcohol solutions containing 10-60 (w/w)% xylitol, D-sorbitol, or glycerol and 1000 ppm fl uoride at room temperature to analyze CaF 2 formation on the surfaces. Only glycerol enhanced fl uoride incorporation signifi cantly and induced a nanoscale spherical deposition on the HA sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…We previously observed that the co‐existence of polyols with F enhances CaF 2 formation on sintered HA plate . In the noted study, glycerol had a stronger effect on CaF 2 formation in comparison to xylitol and D‐sorbitol in the presence of F at neutral pH.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…We previously observed that the co‐existence of polyols with F enhances CaF 2 formation on sintered HA plate . In the noted study, glycerol had a stronger effect on CaF 2 formation in comparison to xylitol and D‐sorbitol in the presence of F at neutral pH.…”
Section: Discussionmentioning
confidence: 61%
“…It has been known that the remineralization is further enhanced if xylitol is used with F ions . We have recently revealed that formation of nano‐scale spherical deposits of phosphorous‐containing calcium fluoride (CaF 2 ) was enhanced on HA surfaces (sintered HA ceramics plates) by various polyols solutions, including xylitol, D‐sorbitol, and glycerol, in the presence of F ions . This noted study suggests that polyols may be capable of enhancing HA surface dissolution and glycerol in particular had the greatest ability with this regard.…”
Section: Introductionmentioning
confidence: 90%